THE LINGUISTIC DEBATES IN BANGLADESH THROUGHOUT HISTORY: A SOCIOLINGUISTIC PERSPECTIVE - Abdul Awal (Galaxy International Interdisciplinary Research Journal, 2021)
From a sociolinguistic perspective, the paper depicts discussions about languages in Bangladesh from the Mughal Period to the present day. For linguistics and human rights, the government’s policies, legislation, and activities relating to language policy in Bangladesh have been criticised. With historical references, the discussions among Bangladeshis over various language concerns are described. The report also attempts to investigate historical arguments concerning foreign language education in Bangladesh among various socio-political and community groups. It also sharply criticises political decisions on linguistic issues, as well as their socio-political consequences. Furthermore, the paper emphasises the importance of creating a democratic language policy in Bangladesh that reflects linguistic human rights.